Gender disparities and associated factors to intention to getting a second dose of COVID-19 AstraZeneca vaccine among adult populations in selected facilities of Lusaka, Zambia. - Choolwe Jacobs; Nedah Chikonde Musonda; Deborah Tembo; Miyanda Simwaka; Evelyn Mwamba; Sody Mweetwa Munsaka; Samson Shumba (Public Library of Science (PLoS), 2022)
As COVID-19 vaccines are becoming more available, there is also a growing need to understand the population receiving the doses, existing inequalities and the intention to getting the second vaccine dose among the populations that receive the vaccines. We evaluated gender inequalities and intention to uptake of the second dose of COVID-19 AstraZeneca vaccine among adult populations in selected urban facilities of Lusaka, Zambia. A cross-sectional study design was conducted between May and June 2021 among adults who received AstraZeneca vaccine from three selected urban facilities of Lusaka, Zambia. Phone-based interviews were conducted 6 weeks after the first dose of the vaccine. Descriptive analysis and mixed-effect logistic regression were done using STATA version 16.2. Of the 1321 adults who had received AstraZeneca vaccine, 868 respondents completed the questionnaire. About, 47% (408/868) were females and 53% (460/868) were males. Median age in the study was 40 years. Majority of males were educated (54%) and employed (57%). Furthermore, majority of females that got the first dose of AstraZeneca reported experiencing side effects (76.98%) compared to males (64.24%). Among study participants, 93.7% intended to receive the AstraZeneca vaccine, of whom 46.7% (380/814) were females and 52.9% (434/814) were males. Majority of participants that did not intend to get a second dose were not married (55.56%). Only age (AOR, 1.05; 95% CI, 1.02-1.08) predicted intention to getting a second dose of AstraZeneca vaccine. We found important gender-dependent differences in the side effects reported by females that received the first dose of Astra Zeneca. Finding that intention to get the second dose of the vaccine increased with age suggests a need for enhancing COVID-19 vaccination programmes targeting young people and a need for further research to identify specific adverse effects of COVID-19 Astra Zeneca vaccines.